Monitoring trends in obesity in South Wales using routine data. Issue 5 (25th April 2005) - Jones, S E; James-Ellison, M; Young, S; Gravenor, M B; Williams, R
Abstract : Aim: To use existing data on height and weight of 5 year old children, routinely recorded annually as part of the school entry medical, to monitor trends in obesity over the last 16 years in three South Wales localities. Methods: Body mass index (BMI) and percentage of children over the cut off points for being overweight or obese proposed by the International Obesity Task Force were determined in 46 073 children who had height, weight, and sex recorded each school year (between 1986/87 and 2001/02) on the National Child Health Computer System held at the Swansea NHS Trust. Results: With the exception of one year, the coverage for BMI measurements ranged between 87% and 99%. The accuracy of measurement and data entry was identified as suspect in some cases, and although some data entry errors could be corrected, 14% of BMI measurements were inadmissible. Logistic regression analysis of BMI trends in the remainder showed that the percentage of 5 year olds classified as overweight or obese had increased significantly over the time period and that the rate of change in girls was significantly greater than that in boys. Conclusion: Overweight and obese children have increased in frequency in this population. The Child Health Computer System is potentially a valuable source of information on the health status of populations and should be capable of monitoring trends in obesity. However, accuracy of measurement and data entry need to be improved, and the system, to be useful on a national basis, needs to be amalgamated at a higher level than individual NHS Trusts.